How Successful is Field Training Program offered by the Public Authority for Applied Education and Training, PAAE&T, Kuwait, in Reducing Dependence on Expatriates? - Al-Ali, Salah (Technium Social Sciences Journal, 2021)
Technical and vocational education would significantly serve the need of developing countries in terms of lower the rate of poverty, reducing the number of people/youth unemployment, ensuring a stable economy, reducing rate of crimes, higher earning, and increasing self-development. It is also essential for the gulf states such as: Kuwait, Qatar, United Arab Emirates, where the lack of skilled and semi-skilled indigenous manpower is notable in essential sectors of their economy (e.g., electricity and water, health care, oil sector, infrastructure). Technical and vocational education is a dual type of educational system that would facilitate the transmission of students into work place. It is considered as a ‘golden” opportunity particularly for youth to be easily employed by industries and business. The success of technical and vocational education would depend, to great extent, on the efficiency of apprenticeship where students spend certain time at industrial premises to gain the required skills. It allows students to experience the real work environment and to interact with machine, devices, and tools applied in industrial production site. This paper examines how successful is the field training program offered by the selected colleges and institutions at the Public Authority for Applied Education and Training, PAAE&T, in providing local industries with indigenous skilled and semi-skilled qualified manpower. The research is based on extensive field work that encompasses a review of the related literature, interviews with sample of heads of supervisors/heads of departments at the Ministry of Health, Ministry of Communications, Ministry of Electricity and Water, and the oil sector in order to assess the quality of field training program. Finally, the research will argue that unless the management of technical and vocational colleges and institutions recognize and appreciate the value of enhancing the quality of field training program with local industries, its contribution in tackling the shortage of skilled and semi-skilled indigenous in essential sectors on the economy will be below the government expectations, thus continuing relaying on expatriates for years ahead.